The Relation Between Village Council (BPD) and Village Government (PEMDES): Conflict, Conspiracy, and Consensus - Kadewandana, Donie (Journal of Rural Indonesia [JORI], 2015)
The aim of study is to analyze the relation between Village Council (BPD) and Village Government (PEMDES). As we know, Village Council or BPD (Badan Permusyawaratan Desa) is a village institution as media to channeling aspirations of rural communities. While Village Government or PEMDES (Pemerintah Desa includes Village Head and Village Authorities) is the executives who run government at the village level. The study findings is indicates that relation of Village Council and Village Head on 1999 to 2004, while the enactment of Law No. 22 of 1999, which at that time BPD was still called as Village Council (Representative) has not worked well since it often emerges a number of conflicts at the village level. The presence of BPD who oversees the village government at that time was often seen as an obstacle to the power of Village Head. Therefore, the village head then used strategies to soften BPD to no longer be a barrier at the end to a pattern of conspiracy. From that power relation is still possible to materialize the consensus pattern that creates peace between each two sides. Then on 2005, when the enactment of Law No. 32 of 2004 and Government Regulation No. 72 of 2005, the escalation of conflict at the village level started to decrease due to the authority of BPD is transformed from Village Council (Representative) to Village Council (Consultative). BPD in those Law is defined as the organizer of Village Government, equally to Village Head. Thus, the intensity from both relations can be integrated.Keywords: village council, democracy, conflict, local politic